41. NUTRITIONAL STATUS OF CHILDREN UNDER 5 YEARS OLD RECEIVING INPATIENT TREATMENT AT THE NATIONAL CHILDREN'S HOSPITAL AND SOME NUTRITIONAL KNOWLEDGE AND PRACTICES OF MOTHERS IN 2023-2024. (Vietnam Journal of Community Medicine, 2025)
Objective: Describe the nutritional status of children under 5 years old receiving inpatient treatment at the National Children's Hospital in 2023-2024 and some nutritional knowledge and practices of mothers taking care of children.Methods: cross-sectional description of 142 children and mothers taking care of children at the Department of Nutrition, National Children's Hospital from December 2023 to April 2024.Results: 19.7% of malnourished children were stunted, 17.6% of malnourished children were underweight, 11.9% of malnourished children were wasted, 3.5% of children were overweight or obese. According to SGNA: 35.9% of children are malnourished. 37.32% of children are anemic. Regarding knowledge: 66.19% of mothers think that babies should be breastfed within the first hour after birth. In practice, 32.39% of mothers breastfeed within the first hour after birth. 85.21% of mothers support breastfeeding babies exclusively for the first 6 months. 47.18% of mothers exclusively breastfed their children for the first 6 months. The percentage of mothers who have knowledge about giving children correct complementary foods and practice giving them complementary foods at the right time is 96.48% and 83.33%, respectively. Conclusion: The malnutrition rate of children under 5 years old receiving inpatient treatment at the National Children's Hospital is quite high. The percentage of mothers with knowledge about breastfeeding and ABS is high, but the percentage of mothers practicing correctly is still low.
Keywords: nutritional status; children under 5 years old; knowledge; nutritional practices of mothers